Backdoor attack detection based on stepping stone detection approach - Al-Minshid, Khalid Abdulrazzaq Abdulnabi (2014)
Network intruders usually use a series of hosts (stepping stones) to conceal the tracks of their intrusion in the network. This type of intrusion can be detected through an approach called Stepping Stone Detection (SSD). In the past years, SSD was confined to the detection of only this type of intrusion. In this dissertation, we consider the use of SSD concepts in the field of backdoor attack detection. The application of SSD in this field results in many advantages. First, the use of SSD makes the backdoor attack detection and the scan process time faster. Second, this technique detects all types of backdoor attack, both known and unknown, even if the backdoor attack is encrypted. Third, this technique reduces the large storage resources used by traditional antivirus tools in detecting backdoor attacks. This study contributes to the field by extending the application of SSD-based techniques, which are usually used in SSD-based environments only, into backdoor attack detection environments. Through an experiment, the accuracy of SSD-based backdoor attack detection is shown as very high.